Dysgraphi Coach: Mobile Application for Dysgraphia Children in Malaysia - Mohd Ariffin, Mazeyanti; Zarith Nabilah Tengku Othman, Tengku; Shakirah Aziz, Nor; Mehat, Mazlina; Izza Arshad, Noreen (International Journal of Engineering and Technology, 2018)
Learning Disability (LD) or Learning Disorders refers to the difficulties of obtaining, processing and storing information in their memory. There are several categories of LD including Dyslexia, Autism and Dysgrahia. The term Dysgrahia refers to learning difficulties which associates to writing skills. Commonly, Dysgrahia occurs to schoolchildren. Researchers proposed that Dysgraphia children could be assisted by using supportive learning tools, however the study on learning tools particularly in mobile application for Dysgrahia is still scarce. Thus, the objective of this paper is to report on the development of a mobile application called DysgraphiCoach as well as its usability testing results. The DysgraphiCoach was constructed by using Evolutionary prototyping approach. In future, DysgraphiCoach will be evaluated in terms of its effectiveness in improving writing skills among the Dysgrahia children.Â Â